Mapping the research bibliometrics in Indonesia with Web of Science (WOS): Trends, Dominant Themes, and Future Directions - Aminudin Aminudin; Alisa Qothrun Nada Rahmah; Mochamad Asep Kuswara; Hanim Husnal Khalidah; Rendi Harmawan (MASI Mandiri Edukasi, 2026)
This research is motivated by the rapid development of scientific publications in Indonesia, which requires systematic mapping to understand the direction of global scientific development. The main objective of this study is to map the bibliometric landscape of research in Indonesia through the Web of Science (WOS) database to identify annual trends, dominant themes, and future research directions. The method used is descriptive bibliometric analysis and network visualization using VOSviewer software on publication data for the period 2004-2026. The research findings indicate a highly exponential growth of publications, reaching a peak in 2025 with a contribution of 35.6% of the total literature. Dominant themes are concentrated in the management, economics, and education clusters, with sustainability and digital innovation emerging as the latest research trends. The National Research and Innovation Agency (BRIN) emerged as the most productive institution, while the field of financial management recorded the highest citation impact. The study's conclusions confirm that research in Indonesia has transformed towards an internationally competitive multidisciplinary approach. Going forward, it is recommended to explore thematic areas with low density to fill the remaining research gaps.